A Cyclin D1‐Specific Single‐Chain Variable Fragment Antibody that Inhibits HepG2 Cell Growth and Proliferation. Issue 8 (29th March 2020) - Wu, Yan; Tang, Weiwei; Cao, Yuhua; Jiang, Dazhi; Zhao, Liangzhong; Zhao, Jialiang; Zhang, Ying; Li, Chengjuan; Cheng, Cheng; Wang, Shuai; Yang, Fang; Zhu, Xun; et al.
Abstract: Cyclin D1 is a key regulatory factor of the G1 to S transition during cell cycle progression. Aberrant cyclin D gene amplification and abnormal protein expression have been linked to hepatocellular carcinoma (HCC) tumorigenesis. Intrabodies, effective anticancer therapies that specifically inhibit target protein function within all intracellular compartments, may block cyclin D1 function. Here, a single‐chain variable fragment (scFv) antibody against cyclin D1 (ADκ) selected from a human semi‐synthetic phage display scFv library is expressed in Escherichia coli as soluble ADκ. Purified ADκ specifically binds to recombinant and endogenous cyclin D1 with high affinity. To enable blocking of intracellular cyclin D1 activity, an endoplasmic reticulum (ER) retention signal sequence is added to the ADκ sequence to encode anti‐cyclin D1 intrabody ER‐ADκ. Transfection of HepG2 cells with expression vector encoding ER‐ADκ elicited intracellular ER‐ADκ expression leading to cyclin D1 binding, significant G1 phase arrest, and apoptosis that are mechanistically tied to decreased intracellular phosphorylated retinoblastoma protein (Rb) levels. Meanwhile, ER‐ADκ dramatically inhibited subcutaneous human HCC xenografts growth in nude mice in vivo after injection of tumors with expression vector encoding ER‐ADκ. These results demonstrate the potential of intrabody‐based cyclin D1 targeting therapy as a promising treatment for HCC. Abstract : A cyclin D1‐specific single‐‐chain variable fragment antibody (ADκ) isolated from a phage antibody library exhibits high affinity and specificity. The endoplasmic reticulum‐retained anti‐cyclin D1 intrabody (ER‐ADκ) interacts with cyclin D1 to block cyclin D1‐‐CDK4 complex function, resulting in downregulation of both Rb phosphorylation and cell cycle‐related gene expression that further leads to phenotypic arrest of hepatocellular carcinoma progression.